Inovasi Layanan Mutu Institusi Pendidikan Kristen: Suatu Tinjauan Integratif - Simanjuntak, Mariana (Sekolah Tinggi Diakones HKBP, 2022)
This integrative study aims to examine and evaluate the relationship between Academic Culture in improving the Quality Innovation of Christian Educational Institutions and the Performance of Christian Educational Institutions; The Process of Knowledge Transfer in improving The Quality Innovation of Christian Educational Institutions and Performance of Christian Educational Institutions and Innovation of Quality of Christian Educational Institutions in improving the Performance of Christian Educational Institutions. This integrative study analyzes and demonstrates that diakonia educational innovation is capable of being a useful tool to improve the effectiveness and quality and performance of Christian educational institutions. The findings of this integrative review show that the integrative review methodology represents a new approach to the field of Christian education management with a very positive and significant impact on institutional performance. The initial design phase makes it possible to describe the process of academic culture creation and knowledge transfer and identify both that directly influence and enhance the Innovation of Christian Educational Quality Services. During this stage, the collaboration of academic culture and knowledge transfer is absolute in the development of innovation in the quality of Christian education. At the modeling stage, Christian education quality service innovation is a mediation that connects Academic Culture and Knowledge Transfer to Institutional Performance. Quality service innovation takes a strong role and proves to be a recommendation to Christian education in achieving competitive excellence. Christian education quality service innovation is essential for experimental science and strong commercial relevance in the context of the dominant logic of technological innovation. The study of the practical implications of quality service innovation focuses on themes such as continuous improvement, project prioritization improvement, customer satisfaction and increased profitability, financial performance, market share and competitiveness. Thus, the versatility of service quality determination is confirmed to be most significant for the performance of Christian educational institutions. Integrative study of quality service innovation affects positively, directly or on the quality and quantity of research quality production, knowledge quality, service quality, education quality, innovation quality, academic quality. The quality of such services will thus affect the quality of investment decisions, educational quality improvement programs, overall quality, image and strategy of Christian education and its relationship to HKBP education.